Матеріали з розкопок поселення трипільської культури біля с. Немирівське Балтського району Одеської області - Відейко, М.Ю. (Археологія і давня історія України, 2010)
Серед матеріалів трипільської культури, які зберігаються у Наукових фондах Інституту археології НАН
України є зібрання знахідок (колекція № 1050) із проведених 1986 року розкопок поселень трипільської культури, які розташовані у басейні р. Кодими на території Одеської області. Вони становлять інтерес, оскільки
походять з малодосліджених у даному регіоні пам’яток
етапу ВІІ. У статті вводяться до наукового обігу матеріали з одного із цих поселень — Немирівського. В Научных фондах Института археологии НАН Украины хранится коллекция материалов (№ 1050) из
раскопок трипольских поселений в Одесской области в
1986 г. проведенных Майданецким отрядом Трипольской экспедиции (начальник М. М. Шмаглий). Материалы исследований уже были опубликованы и учтены исследователями при разработке широкого круга проблем, связанных с изучением памятников трипольской археологической культуры. Коллекция представляет
интерес с разных точек зрения: это одно из немногих
исследованных поселений начала этапа ВII и единственный тут памятник типа Раковца. Последние специалисты рассматривают в качестве основы формирования более поздних комплексов трипольской культуры в междуречье Южного Буга и Днепра. In the Scientific Fonds of the Institute of NAS of Ukraine
there is collection (N 1050), which comes from explorations
of Trypillia Culture settlements at Odessa region,
carried at 1986 by expedition managed by M. Shmaglij.
Some materials were already published and specialists
taking it into account when designing a wide range of
problems, associated with study of different problems of
Trypillia Culture. Collection is interesting from the different
points of view. This is one of the few epplored settlements
of the beginning of BII stage and single place of Rakovetz
type, known at this region. This local type is wery
important, if usually considered as the base for BII stage
local types of Trypillia Culture between the Southern Bug
and Dnipro.